Does the work environment affect designers' creativity during the creative phase depending on their personality profile?. (September 2019) - García-García, Carlos; Chulvi, Vicente; Royo, Marta; Gual, Jaume; Felip, Francisco
Highlights: The study sets out from user's personality influence the way in which the work environment affects designer's creativity. A practical experiment has been performed, using 3 environments during the design process: arousing, relaxing and neutral. Personality profiles were classified based on NEO-FFI personality test. Results point that there is an influence between personality and work environment, mainly in achieving useful results. Abstract: Creativity is one of the fundamental elements to be taken into consideration in the conceptual design phases of the development of new industrial products. It is widely agreed that every individual is creative by nature and that his or her creative capacity may be conditioned by different variables within the work environment. Yet, studies that analyse these variables often treat users in a generalised manner, without paying attention to their specific characteristics. This study sets out from the hypothesis that the user's psychological profile influences the way in which the work environment affects the designer's creativity when addressing the conceptual design phase. Thus, the aim of this study will be to determine whether developing a conceptual design proposal in a "relaxing" or an "arousing" work environment will affect all designers equally or, conversely, it will have a greater effect on some of them depending on their psychological profile. Consequently, the first stage of the study consisted in characterising each member of the control group using the NEO-FFI test. The different users were then distributed into four groups according to the results obtained. In a second phase, each designer developed conceptual proposals for a problem in each of the environments defined for the study. A neutral environment was added as a control element. Subsequently, the CPSS methodology was used to evaluate the creativity of each of the proposals designed in each of the environments. The conclusions from the study show that there is a relationship between some personality profiles and the level of creativity achieved by the designer according to the work environment in which the conceptual proposals have been developed.